2018
DOI: 10.1007/s10980-018-0645-9
|View full text |Cite
|
Sign up to set email alerts
|

Cityscape quality and resource manipulation affect natural enemy biodiversity in and fidelity to urban agroecosystems

Abstract: Context Complex landscapes with high resource availability can support more diverse natural enemy communities and better natural pest control by providing resources and facilitating organism dispersal. Moreover, in agricultural landscapes, local agroecosystem management can support biodiversity maintenance and pest control by adding resources in less complex landscapes with fewer resources. However, we lack an understanding of how local and landscape factors interact to affect natural enemy communities and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…We found that urban gardens are supporting more abundant and diverse ladybird beetle populations in more urban areas in California, while in Michigan, ladybird beetles in urban gardens decline in abundance, species richness and diversity with increasing amounts of impervious cover and faster urbanization rates in most instances. Urbanization is clearly driving the abundance, species richness and behavior of ladybird beetles in California, as we have found in previous studies [29,50]. However, we show that this is not the case in another environmental context (Michigan).…”
Section: Discussionsupporting
confidence: 70%
“…We found that urban gardens are supporting more abundant and diverse ladybird beetle populations in more urban areas in California, while in Michigan, ladybird beetles in urban gardens decline in abundance, species richness and diversity with increasing amounts of impervious cover and faster urbanization rates in most instances. Urbanization is clearly driving the abundance, species richness and behavior of ladybird beetles in California, as we have found in previous studies [29,50]. However, we show that this is not the case in another environmental context (Michigan).…”
Section: Discussionsupporting
confidence: 70%
“…The gardens range in size from 444 to 15,525 m² and serve between 5 and 92 different gardeners (or gardener families). All gardens are managed with organic practices but vary in age (6-40 yrs), local habitat characteristics, i.e., vegetation cover, crop richness, and floral abundance, and landscape surroundings (Egerer et al 2018). The population is ethnically diverse, including recent immigrants (from countries including Mexico, El Salvador, Iran, Bosnia, and Vietnam) and long-time residents of California.…”
Section: Study Region and Sitesmentioning
confidence: 99%
“…The positive correlation between coccinellid abundance observed in our study could therefore also be linked to the higher urbanization levels in HPD, which could have influenced the abundance of aphids (originating from nearby garden floras), and subsequently, coccinellids. Furthermore, Egerer et al (2018b) reported that higher coccinellid abundance and richness was maintained in garden within low-quality cityscapes i.e. areas with more impervious surfaces, thus suggesting that higher levels of urbanization as encountered in HPD would not affect this predatory arthropod group.…”
Section: Discussionmentioning
confidence: 99%